Representasi Toleransi Beragama Dalam Film “Bidadari Mencari Sayap” Karya Aria Kusumadewa Tahun 2020 - Hidayah, Isthiqomah Nurul; Firmansyah, Kholis (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
Indonesia is a country with religious diversity that can unite or divide. This research aims to analyze the representation of religious tolerance in the 2020 film ‘Bidadari Mencari Sayap’ by Aria Kusumadewa using Roland Barthes' semiotic analysis. The film was chosen because it depicts conflict and tolerance between religious communities, which is still an important issue in Indonesia. This literature research uses the film as the primary data source and books on religious tolerance as secondary sources. Data collection was done through literature study and documentation. Data validity was ensured through increased diligence and the use of references. The results showed four values of religious tolerance in the film: respect, respect, agree in disagreement, and sincerity. The film illustrates the implementation of tolerance in society, such as sharing angpao during the lion dance performance, advice on interfaith marriage, and sincere attitude towards differences in beliefs. The research also reveals that sincerity can solve the problem of intolerance, while religious discrimination can trigger conflict. This research provides insight into the importance of religious tolerance in strengthening the unity of the Indonesian nation. Through film analysis, this research highlights the role of media in learning the values of tolerance and understanding between religious communities.